Compensation, radiographic changes, and survival in applicants for asbestosis compensation. Issue 7 (July 1985) - Cookson, W O; Musk, A W; Glancy, J J; de Klerk, N H; Yin, R; Mele, R; Carr, N G; Armstrong, B K; Hobbs, M S
Abstract : The survival of 354 claimants for compensation for pulmonary asbestosis among former workers of the Wittenoom crocidolite mine and mill in Western Australia has been examined. There were 118 deaths up to December 1982. The median time between start of work and claim for compensation was 17 years. The standardised mortality ratio (SMR) for deaths from all causes was 2.65 (p less than 0.0001). The SMR for pneumoconiosis was 177.2 (p less than 0.0001), bronchitis and emphysema 2.6 (p = 0.04), tuberculosis 44.6 (p less than 0.0001), respiratory cancer (including five deaths from malignant pleural mesothelioma) 6.4 (p less than 0.0001), gastrointestinal cancer 1.6 (p = 0.22), all other cancers 1.6 (p = 0.17), heart disease 1.4 (p = 0.07), and all other causes 2.18 (p = 0.004). Plain chest radiographs taken within two years of claiming compensation were found for 238 subjects and were categorised independently by two observers according to the International Labour Organisation criteria without knowledge of exposure or compensation details. Profusion of radiographic opacities, age at claiming compensation, work in the Wittenoom mill, and degree of disability awarded by the pneumoconiosis medical board were significant predictors of survival, but total estimated exposure to asbestos was not. Radiographic profusion and degree of disability were, however, predictable by total exposure. The median survival from claim for compensation was 17 years in subjects with ILO category 1 pneumoconiosis, 12 years in category 2, and three years in category 3.